2009
DOI: 10.4103/0970-4388.55333
|View full text |Cite
|
Sign up to set email alerts
|

An in-vitro comparison of visual inspection, bite-wing radiography, and laser fluorescence methods for the diagnosis of occlusal caries

Abstract: Although accuracy and reproducibility of the LF method were higher than those of the VI and BW radiography, it is better to use this method together with other methods to reduce diagnostic faults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…visual observation, radiography and DD seems though to result to more accurate diagnosis of caries as mentioned also elsewhere. 37 But it should be noted that the actual clinical experience of the operator can affect the objectivity of the detection, either by visual observation or by using devices such as DD. Specifi cally, in a laboratory study, 3 undergraduate dental students, 3 general dentists and 3 academics were asked to evaluate 25 molars by visual observation and by using DD.…”
Section: Accuracy and Repeatability Of Ddmentioning
confidence: 99%
“…visual observation, radiography and DD seems though to result to more accurate diagnosis of caries as mentioned also elsewhere. 37 But it should be noted that the actual clinical experience of the operator can affect the objectivity of the detection, either by visual observation or by using devices such as DD. Specifi cally, in a laboratory study, 3 undergraduate dental students, 3 general dentists and 3 academics were asked to evaluate 25 molars by visual observation and by using DD.…”
Section: Accuracy and Repeatability Of Ddmentioning
confidence: 99%
“…36 Also lecithin/chitosan NPs can be applied to skin cells at concentrations up to 200 µg/ml without inducing plasma membrane damage or cell viability decrease. 37 similarly, in a recent study, HaCaT cells exposed to melatonin containing lecithin/chitosan NPs in a concentration of chitosan of 1.25-20 μg/ml for 2 hours showed no relevant cytotoxicity. 38 However, a significant reduction in the cell viability of HaCaT cells was observed in the case of cells treated with NPs at a chitosan concentration of 20 μg/ml.…”
Section: Original Articlesmentioning
confidence: 53%
“…In permanent teeth, the amount of bacteria detected after conventional caries removal was higher than that which remained in sealed caries lesions. 36 A systematic review and meta-analysis of incomplete caries removal studies 37 concluded that in complete caries removal appeared superior compared to complete caries excavation, especially in lesions very close to the pulp. However, evidence levels are currently insufficient for definitive conclusions because of high risk of bias within the studies.…”
Section: Discussion Of Sealing Dental Caries (Sdc)mentioning
confidence: 99%
See 2 more Smart Citations